Between Hegelian and Marxist thought, a reading in referring the debate from philosophizing to plastic performance (Al-Academy, 2025)
This research is presented between the Hegelian and Marxist philosophies to explore the transition of discourse from philosophy to artistic performance. It aims to demonstrate the effectiveness of the dialectical thought of Hegel and Marx, each with their distinct philosophical approach, and their potential application to the realm of visual artistic performance, which encompasses a variety of ideas, manifestations, compositional structures, and execution materials.The study is divided into four chapters. The first chapter focuses on the methodological framework, addressing the research problem: How can Hegelian and Marxist dialectical thought contribute to the interpretation of visual artistic performance, and how can it create a reciprocal productive relationship within its laws? The significance of the research lies in its contribution to both academic knowledge and aesthetic creativity in the philosophical and artistic fields. It also emphasizes the analytical approach between Hegelian and Marxist dialectical thought. The research’s goal is to uncover the foundations of Hegelian and Marxist dialectical thought with a dialectical orientation in interpreting visual artistic performance.The second chapter introduces the theoretical framework, consisting of three sections: First Section: The concept of dialectics in philosophy, Second Section: Hegelian thought and the transition of discourse from philosophy to artistic performance, and Third Section: Marxist thought and the transition of discourse from philosophy to artistic performance. This chapter also provides indicators for the research.The third chapter outlines the research procedures, including the selection of the research community and the analysis of sample models. Finally, the fourth chapter presents the findings and conclusions. Among the results:1. Dialectics is a mental activity that relies on the interaction between two opposing, conflicting parties. Its effectiveness lies in its ability to uncover and analyze various aspects of existence, including visual art. It aims to challenge the existing and bring about the new, guided by epistemological frameworks for reconstruction, composition, and organization at the highest level of precision.2. Visual artworks, with their diverse and innovative ideas and practical artistic executions, have assisted in interpreting them through the Hegelian and Marxist dialectical thoughts. They have revealed the philosophical and intellectual differences between these two approaches.